Gender differences in diversion among non-medical users of prescription opioids and sedatives - Milani, Sadaf Arefi (Am J Drug Alcohol Abuse, 2020)
BACKGROUND: Non-medical use of prescription drugs is a major public health concern in the United States. Prescription opioids and sedatives are among the most widely abused drugs and their combined use can be lethal. Increasingly rigid prescribing guidelines may contribute to the changing context of opioid use and increase drug diversion. OBJECTIVE: To examine gender differences in diversion of prescription opioids and sedatives among non-medical prescription opioid and sedative polysubstance users. We hypothesize that men will be more likely than women to engage in incoming diversion. METHODS: Data from the Prescription Drug Abuse, Misuse, and Dependence Study, a cross-sectional study focused on prescription drug users, were analyzed. Non-medical use was defined as use of a drug that was not prescribed or use in a way other than prescribed. Individuals who reported past 12-month non-medical opioid and sedative use were included; diversion was defined as incoming (obtaining drugs from a source other than a health professional) and outgoing (giving away/selling/trading prescription drugs). RESULTS: Among the 198 polysubstance users, 41.4% were female. Men were 2.85 times as likely as women to report incoming diversion (95% CI: 1.21–6.72). Women were more likely to obtain opioids from a healthcare professional; men were more likely to obtain sedatives from a roommate, coworker, or friend. Over half of men and women reported outgoing diversion opioids or sedatives. CONCLUSION: Drug diversion highlights an important point of intervention. Current prevention efforts that target prescribers should be expanded to include users and diversion activities; these interventions should be gender-specific.